Auto GMS: An Automated Greenhouse Monitoring System of Abiotic Factors for Leafy Vegetables Production - Anthony, J E S (KnE Social Sciences, 2018)
“Auto GMS: An Automated Greenhouse Monitoring System of Abiotic Factors for Leafy Vegetables Production” was developed to give ease in terms of monitoring or data logging different natural parameters in the greenhouse that affect the crop growth and most importantly, the system was intelligently engineered to automate the traditional watering system in order to prevent the under irrigation and over irrigation. The system is capable of measuring and data logging the soil moisture content, relative humidity, temperature and the light intensity of the greenhouse. The system is equipped with highly sensitive sensors-, relative humidity and temperature sensor, light intensity sensor and the soil moisture sensor to obtain the parameter values and send the notification to the registered number of the greenhouse administrator via SMS, save the data on the SD card in.CSV format as back up, display the findings through LCD screen and send the data and the findings over the cloud service, Thingspeaks, for graphical presentation via WiFi module. Automatic irrigation is highly dependent on the soil moisture threshold and water flow is controlled via solenoid valve and relay. This study employed Developmental, Descriptive Research and Prototyping Model Development. The developed system was perceived by the end users to be very much important in terms of water conservation, energy conservation, plants growth, manpower and load conservation. The system was very much acceptable in terms of usability, functionality, reliability and connectivity and in terms of implementation. Thus, the respondents were convinced that the system can be implemented. Keywords: auto gms, greenhouse, abiotic factors, leafy vegetable, monitoring